2020
DOI: 10.1590/2175-7860202071065
|View full text |Cite
|
Sign up to set email alerts
|

Araceae do Parque Nacional do Caparaó, MG-ES, Brasil

Abstract: Resumo Araceae está entre as famílias com maior riqueza de espécies para o bioma Mata Atlântica e é caracterizada pela presença de inflorescência em espádice, associada a uma bráctea, a espata. Este trabalho tem como objetivo inventariar as espécies de Araceae do Parque Nacional do Caparaó, com chave de identificação, descrições e ilustrações diagnósticas das espécies. Para isso, foram realizadas expedições de coleta nos meses de janeiro, abril e novembro de 2017, em diferentes trilhas, altitudes e formações v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…We classified species as a priority for conservation when they had a single record collected before 1970 (Briggs and Leigh 1988) (ICMBio 2015). Located in "Serra da Mantiqueira", PNC has a wide altitudinal gradient (630 to 2,892 m a.s.l.…”
Section: Sampling Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We classified species as a priority for conservation when they had a single record collected before 1970 (Briggs and Leigh 1988) (ICMBio 2015). Located in "Serra da Mantiqueira", PNC has a wide altitudinal gradient (630 to 2,892 m a.s.l.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…It may be that these species are new occurrences for MG or ES. One recent study, involving the family Araceae in PNC, reported Xanthosoma maximilianii Schott and Philodendron acutatum Schott of these 53 species, as new occurrences for ES and MG, respectively (Camelo et al 2020), emphasising the importance of more in-depth assessments of the occurrence of the other 51 species.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…are those that circumscribe the majority of endemic species (e.g. Croat 1991;Coelho and Croat 2005;Gonçalves 2005;Temponi 2006; Coelho et al 2009;Camelo et al 2018a, b;Coelho and Valadares 2019;Hammes et al 2020;Camelo et al 2020;Coelho et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…O presente estudo foi realizado em Campo de Altitude no Parque Nacional do Caparaó, situado entre as coordenadas 20˚19' a 20˚37' S e 41˚43' a 41˚53' O. Essa unidade de conservação fica localizada na Serra da Mantiqueira, entre os estados brasileiros de Minas Gerais e Espírito Santo e possui 31,8 ha (IBDF, 1981;CAMELO et al, 2020).…”
Section: áRea De Estudounclassified